From violas to violas Ferreira - Amarante, Gabriel Filipe De Castro (2021)
This case is based on a real family business,Grupo Violas,and thepath of Violas Ferreira branch. Consisting of two main chapters, the first is the group’s foundation by its Patriarch and the process incurred till a peaceful asset division in the second generation. The second showcases the evolution of one of the branches, Violas Ferreira, and their Family Office HVF –SGPS. Across the case, several family business concepts are covered more precisely systems theory, the impact of fair process and socioemotional wealth, and Violas Ferreira diversification investments strategies.